SMEs Business Survival Model During the COVID-19 Pandemic: A Case Study of Handicraft SMEs in Bali Province - Ni Luh Wayan Sayang Telagawathi; Ni Made Suci; Ni Made Amanda Dewantini; Ni Kadek Sinarwati (Jurnal Ilmiah Akuntansi, 2024)
Business resilience is essential for MSMEs to survive any crisis. This study examines the factors that influenced the survival of handicraft MSMEs in Bali Province during the COVID-19 pandemic, arguing that their survival heavily depended on pre-existing socio-economic relations. This aligns with previous research indicating that MSMEs, while vulnerable to external pressures, possess socio-economic capital that is often underutilized. The central role of MSME owners and managers is crucial, as is a supportive business environment where business sector actors, local communities, and government collaborate to assist MSME owners and managers. The study finds that weaving SMEs in Bali successfully adapted to their environment, leveraging social capital in the form of social embeddedness. This social cohesion, demonstrated through community and stakeholder support, provided vital social connections that enabled these businesses to withstand the challenges posed by the COVID-19 pandemic. The findings underscore the importance of optimizing socio-economic capital and fostering collaborative support networks to enhance MSME resilience. This research offers valuable insights for policymakers and business leaders aiming to strengthen the resilience of MSMEs in similar contexts, highlighting the need for strategic collaboration and community engagement to support business continuity during crises.